Co-Triggering of Diseases During Transitional Period in Dairy Animals of Punjab - Thakur, Niharika; Singh, Parminder; Kasrija, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was undertaken to determine the predisposition of one transitional disease on the other in various dairy animals of Punjab. For this purpose, a total of 250 respondents were randomly selected and were interviewed personally from various parts of Punjab through a structured interview schedule. Among the various transitional diseases in dairy farms, anoestrus was found to be high (59.00%) followed by mastitis (52.00%).  Dystokia was found to be highly significant (p
Keywords: Dairy animals; Predisposition; Transitional disease